Progredir sempre: os jovens rurais mineiros nos Clubes 4-S: Saber, Sentir, Saúde, Servir - Leonardo Ribeiro Gomes (2013)
This research investigates the propositions for the formation of young rural people around youth organizations called Clubes 4-S (Saber, Sentir, Saúde, Servir) during the period of 1952 to 1974, in Minas Gerais, under the responsibility of the ACAR-MG (Associação de Crédito e Assistência Rural), an institution founded in 1948 with the purpose of implementing the Rural Extension Service in the state. The definition of Rural Extension adopted, comprehended a set of educational activities combining technical assistance and rural credit to small and medium rural owners. According to the documents referred to, the young people from the clubs were considered elements more propitious to changes than their parents. According to the official extensionist speech, adults would be more inclined to refuse scientific innovations and cultural propositions. Therefore, young rural people, considered open to changes, would be multipliers of the transformations intended to their communities. We referred to reports, magazines, mimeographed texts, disclosure brochures, course material, lectures, classes, newspapers, oral assets, photographs and annual programs from ACAR-MG. These sources, in general, feature data related to fields of expertise, technical body, investments, developed projects, financial resources made available by the Government and participating institutions in the extensionist program. Analyzing this data, we could notice the growth of the number of young rural people around the clubs, especially from 1966. However, at the beginning of the 1970´s, the extensionist focus changed, which also caused changes in the work with these young people enveloped in the action philosophy of the Clubes 4-S. We observed that the extensionist action on the young people was based on the formulation of a series of technical prescriptions, moral and civic, seeking to form a kind of young person that stood up to the political and cultural transformations observed in the urban societies in the period between the 1950´s and 1970´s.